Preliminary study on the participation of TLR9 on erythrocyte surface combined with mtDNA in the monitoring of infectious diseases - Xiao, Ling; Xu, Haixia; Liu, Siwei; Cheng, Zhanrui; Kong, Yujie; Tian, Li (Frontiers in Medicine, 2025)
BackgroundTLR9 is typically found within cells and plays a crucial role in identifying pathogenic and self-DNA in chronic inflammation and immune complexes. Recent discoveries indicate its presence on the surface of human red blood cells, where it engages in immune regulation by binding to free mtDNA. The purpose of this study is to explore the role of TLR9 as a pattern recognition receptor combined with mtDNA in the monitoring of infectious diseases.MethodsTLR9 presence on the surface of red blood cells was assessed using flow cytometry in both healthy individuals and patients with bacterial infections. Subsequently, DNA bound to the red blood cell surface was extracted separately from both groups. The absolute quantification of mtDNA copy numbers within the extracted DNA was conducted using qPCR technology, followed by statistical analysis. Additionally, the correlation between mtDNA copy numbers bound to red blood cell surfaces in bacterial infection patients with varying CRP concentrations was examined using univariate linear regression.ResultIn healthy individuals, TLR9 expression on red blood cell surfaces averaged 8.81%. However, the average expression of TLR9 on red blood cell surfaces in patients with bacterial infection was 5.45%, which was lower than that in healthy people (p < 0.001). Notably, both healthy individuals and infected patients exhibited mtDNA binding to red blood cell surfaces, with patients demonstrating a higher mtDNA copy number compared to healthy controls (p < 0.001). Moreover, within the infected group, the copy numbers of mtDNA bound by red blood cells positively correlated with patient CRP concentrations (R2 = 0.715, p < 0.001), indicative of an association between mtDNA copy numbers bound to red blood cell surfaces and infection severity.ConclusionThe elevation of erythrocyte-bound mtDNA during infection, coupled with its correlation with infection severity, suggests that monitoring the copy numbers of mtDNA bound to red blood cells via TLR9 could serve as a novel indicator for infection surveillance.